Pengaruh Kombinasi Foot Massage dan Terapi Murotal terhadap Tingkat Nyeri Pasien Post SC di Ruang Wijaya Kusuma di RSUD Limpung - Karyoto; Linda Nuryanti; Noer Baiti; Putut Parianto (Jurnal Rumpun Ilmu Kesehatan, 2025)
Post-Cesarean Section (C-Section) patients commonly experience pain caused by surgical incisions in the abdominal area. Unmanaged pain may hinder mobility, interfere with breastfeeding, reduce comfort, and negatively affect maternal psychological well-being. Non-pharmacological pain management is considered an alternative to reduce dependence on analgesics. Foot massage has been proven to improve blood circulation, stimulate endorphin release, and reduce pain intensity, while Qur’anic recitation therapy (murottal) provides psychological and spiritual relaxation that helps decrease pain perception. This study aims to examine the effect of combining foot massage and murottal therapy on pain levels in post-C-section patients at Wijaya Kusuma ward, Limpung General Hospital. The benefit of this study is expected to provide a reference for nursing practice, particularly in implementing holistic non-pharmacological interventions to enhance patient comfort. This research employed a case study design with a nursing care approach involving four post-C-section patients. Interventions included a scheduled combination of foot massage and murottal therapy. Pain levels were measured using the Numeric Rating Scale (NRS). Data were analyzed descriptively by comparing pain levels before and after intervention. The results showed a reduction in pain intensity from moderate to mild after the combination intervention. Patients also reported increased comfort, improved rest, and reduced anxiety. In conclusion, the combination of foot massage and murottal therapy effectively reduces pain in post-C-section patients. This intervention can be recommended as a non-pharmacological method in nursing care for post-C-section patients.